Infiltration of the spinal cord and peripheral nerves in multiple myeloma - Su, Xiaoyun; Kong, Xiangquan; Kong, Xiangchuang; Lu, Zuneng; Zheng, Chuansheng (Frontiers in Oncology, 2022)
Background: Multiple myeloma (MM) is a hematological malignancy and intramedullary spinal cord metastasis is extremely rare. Methods: Clinical and radiological data collected from electronic medical records as well as a literature review of reported cases. Results: We report a rare case of IgA-LAM stage IIB MM with involvement of the spinal cord and peripheral nervous system. Laboratory studies showed elevated levels of serum β2- macroglobulin, cerebrospinal fluid protein. Electromyography revealed a demyelinating process with motor conduction blocks. On MRI, the lesions of MM bone marrow characterized as type of diffuse infiltration. MR neurography demonstrated an enhanced nodule in the thoracic segment with swelling of cervicothoracic segments of spinal cord. Moreover, swelling and hypertrophy of the entire nerve branchial, lumbosacral plexus and cauda equina were detected, accompanying by myofascitis and denervated muscles. Ultimately, the patient’s condition deteriorated quickly and died with a diagnosis of refractory MM. Conclusion: MRI not only has the advantage of displaying the primary involved site of the bone marrow, but facilitate detecting extramedullary hematopoietic MM, such as infiltrating site of the central and/or peripheral nervous system.